This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well explained!
@Mahdi Raza you have messed up with your own solution. Latex seems not right
Log in to reply
Probably there would have been some formatting updates from brilliant which might have messed up the LaTeX in the solution. Or maybe it was my mistake. Anyways, thank you for pointing out, I've corrected it
( n + 3 ) 2 = 1 6 ⟹ { n + 3 = 4 n + 3 = − 4 ⟹ { n = 1 [ n < 1 ] n = − 7
⟹ x ( − 7 ) − 1 1 = 3 ⟹ x − 8 1 = 3 ⟹ x 8 = 3 ⟹ x 3 2 = 3 4 ⟹ x 3 2 + ( 7 ) = 3 4 + ( 7 ) ⟹ x 3 2 + 7 = 8 8
Problem Loading...
Note Loading...
Set Loading...
Step 1: Solve for n .
( n + 3 ) 2 n + 3 n ⟹ n = 1 6 = − 1 6 [ n < 1 ] = − 4 − 3 = − 7 .
Step 2: Solve for x .
x n − 1 1 x − 7 − 1 1 x − 8 1 3 1 x 8 ⟹ x = 3 = 3 = 3 = x 8 1 = 3 = ± 3 8 1 .
Step 3: Using x = ± 3 8 1 , find x 3 2 + 7 .
x 3 2 + 7 = ( ± 3 8 1 ) 3 2 + 7 = ( ± 3 ) 8 1 × 3 2 + 7 = ( ± 3 ) 4 + 7 = 8 1 + 7 = 8 8 .